2011
DOI: 10.1016/j.juro.2011.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Pneumoperitoneum Aggravates Renal Function in Cases of Decompensated But Not Compensated Experimental Congestive Heart Failure: Role of Nitric Oxide

Abstract: Decompensated congestive heart failure renders rats susceptible to the adverse renal effects of pneumoperitoneum, a phenomenon that may involve alterations in the renal nitric oxide system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Moreover, they found in another study that rats with decompensated congestive heart failure were more susceptible to the adverse renal effects of pneumoperitoneum when pretreated with L-NAME, implying a higher susceptibility to kidney function deterioration in patients with cardiovascular diseases. 10 The results of our study support these previous studies by showing actual decreases in the expression and activity of eNOS with increasing IAP. This would have resulted in a diminished amount of endothelium-derived NO and thus a decrease in its anti-inflammatory and antioxidant actions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, they found in another study that rats with decompensated congestive heart failure were more susceptible to the adverse renal effects of pneumoperitoneum when pretreated with L-NAME, implying a higher susceptibility to kidney function deterioration in patients with cardiovascular diseases. 10 The results of our study support these previous studies by showing actual decreases in the expression and activity of eNOS with increasing IAP. This would have resulted in a diminished amount of endothelium-derived NO and thus a decrease in its anti-inflammatory and antioxidant actions.…”
Section: Discussionsupporting
confidence: 91%
“… 2 9 On the other hand, pretreatment with NG-nitro-L-arginine methyl ester (L-NAME), an inhibitor of NOS, was shown to aggravate renal ischemia. 2 10 …”
Section: Introductionmentioning
confidence: 99%
“…Concerning the latter, previous studies from our laboratory have demonstrated impairment in NO‐mediated renal vasodilation induced by acetylcholine and the NO donor S ‐nitroso‐ N ‐acetylpenicillamine in experimental CHF,, as well as an attenuated renal and systemic response to atrial natriuretic peptide (ANP) ,. On the other hand, rats with CHF display preserved integrity of the renal NO system, as evidenced by comparable urinary excretion of basal NO 2 +NO 3 compared with sham controls . Likewise, in the current study, we demonstrated that basal urinary excretion of cGMP, the second messenger of NP and NO systems, is preserved in rats with LAD ligation and is even significantly higher in rats with decompensated CHF induced by ACF as compared with sham controls.…”
Section: Discussionsupporting
confidence: 81%
“…These initial studies also demonstrated that rats with decompensated CHF displayed lower urinary excretion of NO 2 +NO 3 in association with reduced glomerular filtration rate (GFR), renal plasma flow (RPF), and urine flow when exposed to elevated IAP, compared with normal controls or compensated CHF animals . Furthermore, nitric oxide (NO) synthase inhibition with nitro‐l‐arginine methyl ester was found to render rats with compensated CHF more susceptible to the adverse renal effects of increased IAP . These findings suggest that perturbations in the generation of cGMP, a second messenger of NO and natriuretic peptides (NPs), may contribute to the deleterious effects of IAP in CHF.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation